2019
DOI: 10.1002/celc.201900854
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Tin Dioxide via (Bi, S) Co‐Doping for Photoelectrocatalytic Reduction of CO2 to Formate

Abstract: Photoelectrocatalytic reduction of CO 2 into useful fuels is a promising approach in terms of climate challenge and energy crisis. In this paper, a novel SnO 2 -based catalyst doped with bismuth (Bi) and sulfur (S) was synthesized via a simple hydrothermal method for photoelectrocatalytic reduction of CO 2 . The as-prepared catalyst demonstrates higher catalytic capability for CO 2 , in which the faradaic efficiency of formate reaches 55.6 % at an overpotential as low as~360 mV and the maximum current density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…For example, Li et al prepared Bi and S codoped SnO x catalysts through a hydrothermal method for PEC CO 2 reduction. [ 107 ]…”
Section: Synthesis Methods For Elemental‐doped Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Li et al prepared Bi and S codoped SnO x catalysts through a hydrothermal method for PEC CO 2 reduction. [ 107 ]…”
Section: Synthesis Methods For Elemental‐doped Catalystsmentioning
confidence: 99%
“…Yupeng et al modified SnO 2 by Bi and S codoping to improve the photoresponse toward CO 2 reduction to formate. [107] The pristine SnO 2 has a polygon structure of ≈10 nm in size, with interplanar distances of 0.247 and 0.325 nm, corresponding to the ( 110) and ( 101) planes. Bi 3þ and S 2À doping to SnO 2 causes decreased interplanar distances to 0.241 and 0.325 nm for ( 110) and ( 101) planes, respectively.…”
Section: Nonmetal-doped Photoelectrodesmentioning
confidence: 99%
“…To boost the photoelectrocatalytic efficiency of pure semiconductors, heteroatoms‐doping into the structure of catalysts has been demonstrated to be an effective approach to facilitate the CO 2 /intermediate activation. Herein, Yang et al reported a Bi, S co‐doped SnO x catalyst for photoelectrocatalytic CO 2 reduction, [ 129 ] which provided abundant active sites and surface defects for formate production, and therefore achieved an ideal CO 2 conversion process with a relatively low overpotential and high partial current density compared with pure SnO 2 catalyst. The Bi, S co‐doped SnO x catalyst showed higher photocurrent density than that of SnO 2 , indicating that the heteroatoms doping could enhance the separation efficiency of photo‐excited electron‐hole pairs and improve the visible‐light absorption ability due to the narrower bandgap.…”
Section: Photoelectrocatalysismentioning
confidence: 99%
“…With respect to Bi and S co-doped SnO 2 electrocatalysts for the CO 2 RR, Li et al utilized a one-step hydrothermal method. 94 Different doping ratios were investigated (0%, 1%, 3%, 5% and 7%), and the FE formate results indicated that 3% doping was the best enabling a FE formate of 55.6% at −1.0 V vs. Ag/AgCl. Noticeably, this (Bi, S) co-doped SnO 2 was also capable of functioning as an effective photocatalyst, signifying that the development and design of catalysts with bifunctionalities ( i.e.…”
Section: Binary Bisn-based Electrocatalystsmentioning
confidence: 99%